Visionary Ventures: Cultivating Sustainable Entrepreneurship Across Cultures - Maspul, Kurniawan Arif (Journal of Economics and Economic Education, 2024)
The demand for sustainable business practices is higher than ever in today's world, which is characterised by environmental degradation, social inequity, and economic unpredictability. Sustainable entrepreneurship, which balances economic, social, and environmental aims, can lead to more ethical and resilient organizational operations. This study dives into the transformative journeys of Howard Schultz of Starbucks and Edward Tirtanata of Kopi Kenangan to show how businesses can succeed while solving global concerns. Schultz's vision of Starbucks as a "third place" between home and work, influenced by Italian coffee culture, and Tirtanata's purpose to make high-quality coffee accessible and culturally relevant in Indonesia demonstrate visionary leadership and market adaptation. Their encounters show how incorporating sustainability into fundamental business strategy may improve brand reputation, strengthen supply chains, and fulfil the growing consumer demand for corporate responsibility. This study explores the socio-theoretical foundations and worldwide goals of sustainable business using qualitative analysis, which includes a literature review and thematic coding. It emphasizes the significance of cultural sensitivity and community inclusion, emphasizing how honouring local traditions generates more market acceptance and community bonds. The study also coincides with strategic management theories including the resource-based view (RBV), planned behaviour theory, and stakeholder theory, emphasizing the link between sustainability and intrinsic motivation and purpose. Ultimately, Schultz and Tirtanata's experiences demonstrate that sustainable entrepreneurship is more than a moral duty; it is a strategic necessity for long-term success.